(untitled) (Vietnam Journal of Community Medicine, 2025)
We compared the bioavailability of nano-selenium prepared using green nanotechnology from herbal extracts with conventionally synthesized nano-selenium and raw selenium (non-nanoparticulated) in an experimental animal model. Blood samples containing arsenic were analyzed by atomic absorption spectroscopy, with the method validated according to ICH and AOAC guidelines. The validation results demonstrated that the analytical method exhibited high sensitivity, specificity, broad linear range, accuracy, precision, and excellent stability. This validated method was then applied to evaluate the bioavailability of selenium in both nano-selenium formulations and conventional selenium samples. The findings revealed that plasma-synthesized nano-selenium showed absorption efficiency comparable to that of green-synthesized nano-selenium, with both formulations demonstrating significantly higher bioavailability than conventional bulk selenium. These preliminary results suggest the promising potential of green nanotechnology for selenium nanoparticle synthesis compared to traditional preparation methods.